Estimasi Kedalaman Batuan Dasar di Kampung Yabaso Kabupaten Jayapura Menggunakan Metode Vertical Electrical Sounding Konfigurasi Schlumberger dan Metode HVSR - Asmuruf, Andy Amus Saul; Baru, Netty Y.; Kareth, Zakaria Victor (Jurnal Fisika Papua, 2023)
Research on the estimation of bedrock depth in Yabaso village, Jayapura district using the Schlumberger configuration Vertical Electrical Sounding (VES) method and the HVSR method has been carried out. The total observation points are three points where VES is one point and VHSR are two observation points. VES measurements used a set of resistivity meter model AK HV 500 with a maximum spread length of the current electrode is 100 m. HVSR measurements use a portable seismograph set and the measurement time for ambient seismic waves is 60 minutes. VES and HVSR data processing respectively using IPI2Win and Geopsy software. The model parameters resulting from the inversion of the VES data show that there are nine layers with a resistivity range between 18 – 25,260 Ωm. Layer 1 is a heap of sandy gravel with a resistivity value of 92 Ωm. Layers 2 to 7 are part of alluvium formations and coastal deposits (Qa) with resistivity values of 18 – 264 Ωm. While layers 8 and 9 are fragments of weathered ultramafic rock (um) and compact and dry ultramafic rock respectively. The source rock (bedrock) is layer 9 which is at a depth of 42 m. The results of HVSR data processing show that the natural frequencies at the two observation points are very small (<2.5 Hz), namely 0.85 Hz and 0.83 Hz. According to Kanai's classification, this frequency value is type I, class IV, namely alluvial rock. The depths of source rock based on the HVSR method at measurement points 1 and 2 are 43 m and 44 m, respectively. There is agreement in the estimation of the depth of the source rock obtained from the VES and HVSR methods even though the two methods utilize two different physical parameters. Keywords: HVSR; VES configuration Schlumberger; Resistivity; Jayapura